2020
DOI: 10.1177/1941738119898210
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Quadriceps Muscle Morphology Before and After Anterior Cruciate Ligament Reconstruction and Its Associations With Patient-Reported Outcomes

Abstract: Background: Reductions in muscle size are common after anterior cruciate ligament reconstruction (ACLR) and may contribute to suboptimal patient outcomes. However, few studies have quantified postoperative alterations in muscle quality and evaluated its associations with patient-reported function. Hypotheses: Rectus femoris cross-sectional area (CSA) will decrease postoperatively but improve at return to activity (RTA), rectus femoris muscle quality (percentage fat [PF]) will increase postoperatively and be gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
2
9
1
Order By: Relevance
“…In addition, this study demonstrated slightly smaller vasti muscle volumes compared with a normative database (<1 SD) 83 of uninjured individuals. These findings appear to be supported by several investigations [84][85][86] reporting no between-limb differences in rectus femoris CSA or volume after ACL injury. However, volumetric differences do not appear to be uniform between muscles or within a single muscle, as the collective evidence of individual muscle impairments is conflicting.…”
Section: Morphological Changessupporting
confidence: 82%
See 4 more Smart Citations
“…In addition, this study demonstrated slightly smaller vasti muscle volumes compared with a normative database (<1 SD) 83 of uninjured individuals. These findings appear to be supported by several investigations [84][85][86] reporting no between-limb differences in rectus femoris CSA or volume after ACL injury. However, volumetric differences do not appear to be uniform between muscles or within a single muscle, as the collective evidence of individual muscle impairments is conflicting.…”
Section: Morphological Changessupporting
confidence: 82%
“…A 21% reduction in rectus femoris CSA has been observed in the injured limb and to a lesser degree in the contralateral limb (12%) 9 weeks after surgery. 84 Likewise, an increase in quadriceps volume asymmetry has been observed from presurgery (6% asymmetry) to 4 (19% asymmetry) and 12 (17% asymmetry) weeks post-ACLR. 88 Small-to-large deficits in quadriceps CSA and volume appear to persist from 6 months to 5 years post-ACLR.…”
Section: Morphological Changesmentioning
confidence: 85%
See 3 more Smart Citations